The Vital Transgression of Claudio Rodríguez Fer (Global Journal of Human-Social Science, 2023)
The main aim of this article is to analyze how gender relations power and violence are manifested in the literature of Galician writer Claudio Rodr guez Fer through some significant texts in prose and verse the short story A muller loba from the book Contos e descontos and some poems with erotic and social themes In 2011 the author titled a collection of his poetic work Amores e clamores Loves and cries because these are the two great themes that run through his literature and his life On the one hand erotic passion and on the other cries against injustice oppression dictatorships and his vital and poetic solidarity with the victims of all kinds of repression and with the integral freedom of all beings